Rare coinheritance of hemoglobin vancleave with severe beta-thalassemia mutation in a patient with secondary erythrocytosis - Nur Aisyah Aziz; Nurul Hidayah Musa; Melina Mathews; Komalah Thevii Rajenderan; Faidatul Syazlin Abdul Hamid; Syahzuwan Hassan; Syahira Lazira Omar; Wan Nurul Afiqha Binti Wan Yusoff; Melanie Ling Binti Mohd Din; Nurul Amira Binti Jamaludin; Wan Rohani Wan Taib; Ezalia Esa; et al. (Human Genome Variation)
Abstract Hemoglobin (Hb) Vancleave (NM_000518.5:c.431 A > T; dbSNP: rs33918338) is an extremely rare structural hemoglobin variant worldwide, and studies are limited. This report describes the case of a 16-year-old male patient who presented with secondary erythrocytosis. The diagnosis of Hb Vancleave, in combination with codon 41/42 (-TTCT) (NM_000518.5:c.126_129del; dbSNP: rs80356821), was confirmed by direct sequencing. This report highlights the importance of sequencing in the differential diagnosis of beta-thalassemia syndrome in Malaysia.